Hidden-Order dan Hidden-Power pada Ruang Terbuka Publik, Studi Kasus: Lapangan Cikapundung, Bandung - Rr. Dhian Damajani (ITB Journal Publisher, LPPM ITB, 2007)
One approach to understand urban space is by observing daily activities in the public space. By identifying the complexity of events in everyday activities, we can understand how meaningful an urban space is. In order to optimize the use of public space, we can identify its use on 24 hours time-span when several actors participate in sharing roles, spaces, and time in conducting commercial activities. Results of observation indicate that hidden-order can be identified as structured activities by order while hidden-power as controlled activities by social agreement. Both components serve as important elements for